(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Many studies indicate that the irregularity of the bundle of output sliver was caused by the irregular action of the fibers in the drafting zone. In this research, each staple fiber length of the bundle in the back roll nip and the accelerated points of every fiber in this bundle were generated by using Monte Carlo method according to the theories of the density function of the length distribution using nonparametric kernel estimation method and parabolic-type probabilistic density function of accelerated points distribution. The profile changes of the fiber number in cross section of the bundle in drawing process was simulated, and the various states of the bundle and the attenuation curve of bundle in the drafting zone were obtained. The profiles of the state curves of the bundle changes shows a turning area obviously and the profiles of the attenuation curve experienced a jerk near the front roll, which caused irregularities in the linear density of the output sliver.